Pemberian Terapi Akupresur terhadap Gangguan Mobilitas Fisik pada Pasien Stroke Iskemik dengan Hemiparesis Sinistra di RS Mardi Rahayu Kudus - Ellena Virgin Cindy Puspita; Sri Puguh Kristiyawati (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Physical mobility impairment refers to limited physical movements from one or more extremities independently, this condition can lead to significant difficulties in movement and the inability to perform daily activities. This study aims to apply acupressure therapy to address physical mobility impairment in Mrs. N, a patient diagnosed with ischemic stroke and left-sided hemiparesis at Mardi Rahayu Hospital, Kudus. The method used in this study is a case study involving nursing care and the implementation of interventions, including assessment, diagnosis, planning, implementation, and evaluation, as well as the application of acupressure therapy. The result of the case study acupressure therapy intervention for 7 days at a frequency of once daily for 15 minutes, it was effective in addressing the problem of physical mobility impairment in the patient with ischemic stroke and sinistra hemiparesis, as indicated by increased muscle strenght. The conclusion from this acupressure therapy is that before the intervention, it improved to and after the intervention . It is expected that this acupressure therapy can be applied and integrated into the provision of medical-surgical nursing care for patients with ischemic stroke and sinistra hemiparesis.